Masalah Sosial dalam Novel Rembulan Tenggelam di Wajahmu Karya Tere Liye: Kajian Sosiologi Sastra - Syafrona, Andrika; Abdurahman, Abdurahman; Nst., M. Ismail (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2013)
The purpose of this study the social problem, the causes of social problems, and other forms of self-acceptance to the problems faced by characters in the novel RembulanTenggelam di Wajahmu byTereLiye. The data of this study are the sentences, either in the form of dialogue, monologue, or narrative-related social problems contained in the novel RembulanTenggelam di Wajahmu by TereLiye. Sources of data in this study is novel Rembulan Tenggelam di Wajahmu by TereLiye. The study's findings are: First, the social problems include crime of violence in the form of violence against children, crimes against women, family disorganization, delinkuensi children, gambling, alcoholism, prostitution, and fights. Second, the causes of social issues: family disorganization, lack of public awareness, and adolescent delinquency. Third, self-acceptance prominent social issues in accordance with the problem at hand.